Lipopolysaccharide로 유도된 RAW264.7 세포에서 발효도라지추출물의 항염증 상승효과 물질 탐색 - 송희원(Hee Won Song); 이소연(Soyeon Lee); 한은혜(Eun Hye Han); 유희종(Heui Jong Yu); 임미경(Mi Kyung Lim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2019)
도라지(Platycodon grandiflorum)는 우리나라 및 중국, 일본에서 자생하고 있는 다년생 초본류로서 항염, 천식, 항비만, 항암, 고지혈증 개선, 피부염 개선 등 다양한 효능을 보유하고 있으며, 예로부터 약용 및 식용으로 널리 이용되었다. 본 연구에서는 도라지를 이용한 건강식품 개발의 효율성을 높이기 위하여 도라지의 유효성분으로 알려진 platycodin D 함량을 높이고, 도라지추출물과 혼합하여 상가･상승효과를 낼 수 있는 물질을 발굴하고자 하였다. 따라서 본 연구에서는 14종의 천연물 추출물과 6종의 미네랄, 11종의 비타민에 대한 NO 생성 억제능을 확인하였으며, 이로부터 대두추출물, 달단메밀추출물, 당귀등복합추출물, 비타민 C 4종을 선별하였다. 이들을 발효를 통해 platycodin D 함량이 4배 증가한 발효도라지추출물과 조합하여 RAW264.7 세포에 농도별로 처리하여 LPS에 의해 유도된 NO를 생성 억제율을 측정하였다. 실험 결과 대두추출물과 비타민 C는 발효도라지추출물 200, 400 μg/mL와 조합한 농도에서 발효도라지추출물 단독 처리군 대비 각각 85.5%, 79.3%, 76.3%, 60.9% 증가한 NO 생성 억제율을 보여 발효도라지추출물과 대두추출물 또는 비타민 C의 복합물에 의한 상승효과를 확인할 수 있었다. 반면에 달단메밀추출물은 발효도라지추출물과 상승･상가효과는 보이지 않았으며, 당귀등복합추출물의 경우에는 NO 생성 억제 효능이 1,600 μg/mL 농도의 발효도라지추출물에서만 38.8% 증가하였다. 또한 MTT assay를 수행하여 발효도라지추출물과 대두추출물, 달단메밀추출물, 당귀등복합추출물, 비타민 C 복합물에 의한 세포생존율을 확인한 결과 발효도라지추출물과 달단메밀추출물, 당귀등복합추출물의 조합에서는 세포생존율에 영향을 미치지 않았으나, 발효도라지추출물 1,600 μg/mL 농도에서 대두추출물과 비타민 C와의 복합물에서 세포생존율이 각각 71.8%, 82.9%로 감소하였다. 따라서 발효도라지추출물 농도는 최소한 1,600 μg/mL 이하로 설정하되, 200~400 μg/ mL의 발효도라지추출물과 1 mg/mL의 대두추출물 또는 100 μg/mL의 비타민 C와의 조합이 항염작용의 상가･상승효과를 낼 수 있는 최적의 조합으로 생각된다. 이러한 연구 결과는 기능성이 증진된 제품 개발을 위한 기초자료로 활용될 수 있을 것으로 생각된다. The root extracts of Platycodon grandiflorum (PG) have been widely used as a phlegm-relieving herb. Platycodin D, derived from the root of P. grandiflorum, is known as an effective ingredient and possesses a variety of pharmacological effects such as anti-asthma, anti-inflammation, anti-obesity, anti-cancer, antimicrobial and immunomodulatory activities. This study aimed to find substances that could have an additive or synergistic effect on anti-inflammatory activities when combined with fermented P. grandiflorum extracts (FPG) containing increased platycodin D contents due to fermentation. Nitric oxide (NO) assays were performed using 14 natural product extracts, 6 minerals, and 11 vitamins. Among them, four substances, namely tartary buckwheat extracts, angelica (root) complex extracts, soybean extracts, and vitamin C, were selected for combination with FPG. As a result, soybean extracts and vitamin C exhibited additive or synergistic anti-inflammatory effects in combinatorial treatment with FPG, whereas tartary buckwheat extracts and angelica complex extracts did not exert synergistic effects. The combinatorial treatment of 200 μg/mL of FPG with soybean extracts or vitamin C inhibited NO production in LPS-stimulated RAW264.7 cells by 85.5%, and 76.3%, respectively, compared to treatment with FPG alone. In addition, combinatorial treatment of FPG with tartary buckwheat extracts or angelica complex extracts did not affect cell viability, however combinatorial treatment of 1,600 μg/mL of FPG with soybean extracts or vitamin C reduced cell viability. Therefore, these findings may be used as a basis for developing products with enhanced anti-inflammatory functionality using fermented P. grandiflorum extracts. KCI Citation Count: 2